Experimental drugs in randomized controlled trials for long-COVID: what’s in the pipeline? A systematic and critical review - Yong, Shin Jie *; Halim, Alice; Halim, Michael; Long, Chiau Ming *; Goh, Khang Wen; Alfaresi, Mubarak; Alsalem, Zainab; Alwashmi, Ameen S S; Khamis, Faryal; Al Kaabi, Nawal A; Albayat, Amal; Alsheheri, Ahmed; et al. (2023)
Introduction: Over three years have passed since the emergence of coronavirus disease 2019 (COVID-19), and yet the treatment for long-COVID, a post-COVID-19 syndrome, remains long overdue. Currently, there is no standardized treatment available for long-COVID, primarily due to the lack of funding for post-acute infection syndromes (PAIS). Nevertheless, the past few years have seen a renewed interest in long-COVID research, with billions of dollars allocated for this purpose. As a result, multiple randomized controlled trials (RCTs) have been funded in the quest to find an effective treatment for long-COVID.